Understanding the sensory perception of hydrocolloid thickened systems based on flow and lubrication behaviour - He, Qi (2014)
This thesis seeks for a better understanding of the sensory properties of hydrocolloid thickened foods during oral processing through studying both flow and lubrication behaviours. In addition, during oral processing, saliva plays an important part through mixing with samples, and it is therefore the mixture of foods and saliva that is perceived. However, the role of saliva in sensory perception is not fully elucidated. This research also features a preliminary study on both flow and lubrication properties of saliva in presence of the 5 basic tastants and also how lubrication properties of hydrocolloids are changed when mixing with saliva. Two groups of five samples were designed to have either similar viscosity at a shear rate of 50 s-1 or 105 s-1 by varying the concentrations of xanthan and dextran with the aim to find out which shear rate(s) is related to mouthfeel perceptions. Samples had the same levels of sucrose and banana flavour (isoamyl acetate) added to them and the flavour release and in mouth perceptions measured. The flow behaviour of samples were further characterised in small amplitude dynamic oscillatory shear and stretch flow. A trained sensory panel generated and evaluated mouthfeel, aroma and taste attributes of these solutions. Sensory results indicated that both low and high shear viscosity were related to mouthfeel perceptions. Models including both low and high shear viscosity values predicted the ‘Thickness’ perceptions better than the models including a single shear viscosity. Stickiness and mouthcoating perceptions were better predicted through models including both low shear viscosity and extensional viscosity. Mouthfeel perceptions were also found to be related to complex viscosity at angular frequency of 100 rad.s-1. In terms of sweetness perception, it was affected by the low shear viscosity. However, for samples having similar low shear viscosity, higher scores of overall sweetness were given to samples that were less shear thinning. The high shear viscosity of hydrocolloid samples determines the lubrication properties. Samples with higher viscosity at high shear rate were found to have lower friction in mixed regime but higher in hydrodynamic regime. The mouthfeel perceptions were found to be correlated with friction coefficient at speed of 40-100 mm/s and flavour and aroma were negatively correlated with friction coefficient at speed of 10-30 mm/s. The flow and lubrication behaviour of saliva is changed significantly when stimulated by five basic tastes. The presence of saliva mixed with hydrocolloid samples reduced the friction by up to two orders in boundary and mixed regime but did not affect the friction in hydrodynamic regime which is more related to mouthfeel perceptions.